Benzoic acid formation and its relationship with microbial properties in traditional Turkish cheese varieties. (June 2021) - Yerlikaya, Oktay; Gucer, Leyla; Akan, Ecem; Meric, Saban; Aydin, Emel; Kinik, Ozer
Abstract: Benzoic acid, the simplest member of the aromatic carboxylic acid family, is a weak acid that is a precursor to the synthesis of many important organic compounds. In addition to being used to prevent microbial spoilage in foods, it can also form due to different factors in foods. Hippuric acid found in the natural content of milk can be converted into benzoic acid naturally and can be found in different levels in dairy products. The present study aimed to determine the naturally-forming benzoic acid values in fresh and ripened traditional type cheese varieties and to determine the effect of some physicochemical and microbiological changes of cheeses on the amount of benzoic acid. In this research, benzoic acid levels of six different cheese types (White pickled cheese (traditional-industrial), Tulum cheese (canned or goat skin-packed), and Kashar cheese (fresh and ripened)) were determined. As a result of the analysis performed by HPLC, the amount of benzoic acid in cheese samples varied between 5.95 and 55.72 mg/kg, and it was determined that the microbiota of cheese significantly affected the formation of benzoic acid ( p < 0.05). Especially, a lower benzoic acid level was observed in fresh Kashar and industrial White pickled cheeses with short shelf life, whereas a higher shelf-life was observed in cheese types such as ripened traditional White pickled and skin-packed Tulum cheese ( p < 0.05). Although there is a difference according to the cheese types, especially between hippuric acid content and changes in pH, and Lactococcus and Enterococcus, a correlation was found between benzoic acid content and yeast-molds changes.